Scrotal Hypospadias with Severe Chordee, Micropenis, and Bifid Scrotum in A Child Treated with Multi Stage Repair and Hormonal Therapy - Paulina Magdalena; Gede Wirya Kusuma Duarsa (Neurologico Spinale Medico Chirurgico, 2019)
Proximal hypospadias, include proximal penile, penoscrotal, scrotal and perineal types, are a less common occurrence and correspond to 20% of total hypospadias. Surgical reconstruction is the only possible therapeutic option for hypospadias. The primary objectives of the reconstruction are to create a vertically slit orthotopic meatus, straighten the penis and establish good cosmetic results that include a conically shaped glans. Other important aspects for the reconstruction are to avoid shortening the penis and optimal skin coverage. A 9 years old male presented with abnormal spraying during urination. The parents said that the opening of his urethra is located under the penis. Everytime he urinates, the urine flowing along the thighs. In physical examination, the opening of urethra is in the scrotum. The penis was uncircumcised while the scrotum was bifid in the normal position, and bilateral testes were fully descended in the well-developed scrotum. Repair of proximal hypospadias involves correction of several components of the hypospadias complex with the intent of optimizing long-term functional and cosmetic outcomes. These components include ventral penile curvature, proximal location of the urethral meatus, ventral skin deficiency, glans morphology abnormality, abnormal division of the corpus spongiosum, penile torsion and penoscrotal transposition. Surgical correction of several components divide into five sequential steps. Severe forms of hypospadia are typically accompanied by an abnormal ventral curvature of the penis (chordee). Surgical correction of both chordee and hypospadias is recommended. When properly corrected, it does not cause long-term problems, and a natural appearance of the penis is usually restored.